1974
DOI: 10.1128/aac.6.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Deactoxycephalosporin C by a Mutant of Cephalosporium acremonium

Abstract: A number of Cephalosporium acremonium mutants blocked in the synthesis of cephalosporin C were investigated for accumulation of other ,3-lactam compounds. The non-cephalosporin C producers were isolated after exposing the superior cephalosporin C-producing strain M8650-4 to ultraviolet light (268 nm). One of the blocked mutants, MH63, accumulated deacetylcephalosporin C (0.4 mg/ml), deacetoxycephalosporin C (1.5 mg/ml), and penicillin N (2.7 mg/ml). In contrast, the parent of MH63 produced high levels of cepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Mutants blocked in the fi nal steps in cephalosporin biosynthesis were isolated. Some of them accumulated deace tylcephalosporin C (42, 45), and others were found to accumulate deacetox ycephalosporin C (44,107) in the fermentation broths. Cell-free extract of the parent strain converted deacetoxycephalosporin C into cephalosporin C, but extracts of the blocked mutants were incapable of this conversion (41,43).…”
Section: Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Mutants blocked in the fi nal steps in cephalosporin biosynthesis were isolated. Some of them accumulated deace tylcephalosporin C (42, 45), and others were found to accumulate deacetox ycephalosporin C (44,107) in the fermentation broths. Cell-free extract of the parent strain converted deacetoxycephalosporin C into cephalosporin C, but extracts of the blocked mutants were incapable of this conversion (41,43).…”
Section: Biosynthesismentioning
confidence: 99%
“…For a long time only a few strains of molds had been known to produce ceph alosporin C. Recent studies using ,8-lactam-super-susceptible mutants of bacteria (72,74,77) have demonstrated, however, that a considerable num ber of genera of eukaryotic fungi other than Cephalosporium or Emericel [opsis produce cephalosporin C and related compounds. Reports are accumulating on the fermentation production of cephem compounds by wild isolates and also by mutant organisms derived from cephalosporin C-producing strains (42,52,66,68,73,107,121) (Table 2). Production of cephalosporins from n-paraffin was also reported (75).…”
Section: Occurrence Of Penicillins and Cephalosporinsmentioning
confidence: 99%
“…Mutation and medium manipulation with the nebramycin-producing organism Streptomyces tenebrarius, a culture producing a number of nebramycin components, yielded a variety of strains, some of which elaborated a single component in fermentations (Stark et al, 1971). In a series of mutants which were blocked in the synthesis of cephalosporin C, strains were encountered which synthesized enhanced levels of deacetoxycephalosporin C as well as deacetylcephalosporin C (Queener et al, 1974). Streptomyces noursei produces cycloheximide and the unrelated metabolite, nystatin.…”
Section: E Mutation To Nonproduction Of Undesirable Metabolites and mentioning
confidence: 99%
“…All CPCmutants (102,104,105,179,241) fall into three classes, accumulating PCN, DOCPC, and DCPC; PCN and DOCPC; or PCN only. This is consistent with a linear biosynthetic pathway: PCN -+ DOCPC --CPC.…”
Section: "Low Specificity" Of Secondary Metabolicmentioning
confidence: 99%